Pyroelectric Synthesis of the Site‐Specific Au‐ZnO Nanorod Array. Issue 41 (2nd November 2021) - Wang, Liren; Wang, Han; Wang, Xinyu; Tao, Peng; Shang, Wen; Fu, Benwei; Song, Chengyi; Deng, Tao
Abstract: This paper introduces an alternative approach for the synthesis of site‐specific gold‐zinc oxide (Au‐ZnO) nanorod array through the pyroelectric approach. The hydrothermally grown ZnO nanorod array on the Si substrate is served as the pyroelectric catalyst. Under rapid temperature oscillation, the gold salt precursor is reduced into gold nanoparticles around the tip of ZnO nanorods in aqueous solution. The hybrid structure shows a significant photoluminescence quenching in the visible emission spectrum of ZnO, which is due to the interaction of ZnO and gold nanoparticles. A Rhodamine B (RhB) degradation test under full spectrum sunlight illumination is conducted to demonstrate the photocatalytic performance of the Au‐ZnO nanorod array. The mechanism behind the hydrothermal growth of ZnO, pyroelectric reduction of gold nanoparticles, and photoluminescence quenching of Au‐ZnO is discussed. The findings of this work offer possible ways to the sustainable use of thermal energy, including harvesting waste heat through pyroelectric effect, and the site‐specific synthesis of various nanomaterials with enhanced photocatalytic degradation capability. Abstract : Pyroelectric synthesis offers an alternative approach for the site‐specific synthesis of gold‐zinc oxide nanorod array. The gold nanoparticles are reduced around the tip of the zinc oxide nanorods, and the synthesized hybrid nanocomposite shows an enhance photocatalytic property performance than pristine zinc oxide nanorods.